Development of Spatial-System Dynamics Model for Food Security Policy in Indonesia: A Generic Sub-Model Simulation - Avianto, Teten W; Putro, Utomo Sarjono; Hermawan, Pri (SBM ITB, 2017)
Abstract. The Indonesia has the immense geographic condition and heterogeneous condition, therefore food security issues could not be aggregated nationally, instead, they have to be described per region. In this paper, the region is defined as a province. Food security issues in every region are dynamic, and generated with complex system structure, will be described in the paper as follows. First, in order to have the comprehensive description of food security, we develop a new spatial system dynamics model that combines the concept of space and time. Previous spatial system dynamics methods could only describe the dynamics of the natural/physical system. The new spatial system dynamics proposed in this paper is designed to accommodate human decision for policy intervention. Then, we develop a decision support system, as follow. (1) After comparing characteristics of each province, we can identify the similarity of all province. We call the similarity as the generic model. (2). We propose a new method of spatial system dynamics that can accommodate the immense geographic condition and the heterogeneity. (3) By combining the generic model and the new method we propose a comprehensive model for decision support system in food security policy. Finally, from the experiments with a simulation of the comprehensive model, we could understand that a policy intervention of food security could give impact differently toward each region. Keywords: System dynamics, spatial system dynamics, food security, modeling, policyAbstrak. Indonesia mempunyai kondisi geografis yang membentang sangat luas dan heterogen, oleh karena itu persoalan ketahanan pangan tidak dapat diagregasikan secara nasional, tetapi harus dirinci per wilayah. Di paper ini satu wilayah itu representasi suatu provinsi. Persoalan ketahanan pangan suatu wilayah itu dinamis, dan dimunculkan oleh struktur sistem yang kompleks, yang akan dipaparkan dalam paper ini sebagai berikut ini. Pertama, agar dapat mendeskripsikan ketahanan pangan secara komprehensif, kami mengembangkan suatu model spatial-system dynamics baru yang memadukan konsep ruang dan waktu. Metodologi ini sebelumnya hanya bisa menggambarkan sistem fisik. Spatial-system dynamics baru yang diusulkan di paper ini didisain untuk mengakomodasi pemodelan keputusan manusia untuk intervensi kebijakan. Kemudian, kami membangun suatu sistem pendukung keputusan, sebagai berikut ini. (1) Setelah membandingkan karakteristik tiap provinsi, kita dapat mengidentifikasi kesamaan di antara seluruh provinsi. (2) Kami mengusulkan metode spatial-system dynamics baru yang dapat mengakomodasi kondisi geografi yang membentang sangat luas dan heterogen. (3) Dengan mengkombinasikan model generik dengan metode baru, kami mengajukan gagasan suatu model komprehensif untuk sistem pendukung pembuatan keputusan dalam hal kebijakan ketahanan pangan. Akhirnya, dari hasil simulasi model yang komprehensif kita dapat memahami bahwa suatu intervensi kebijakan pangan dapat berdampak berbeda beda dari satu wilayah dengan wilayah lainnya.Katakunci: System dynamics, spatial system dynamics, ketahanan pangan, pemodelan, kebijakan